Paired Primary and Metastatic Tumor Analysis of Somatic Mutations in Synchronous and Metachronous Colorectal Cancer - Kim, Kyu-pyo; Kim, Jeong-Eun; Hong, Yong Sang; Ahn, Sung-Min; Chun, Sung Min; Hong, Seung-Mo; Jang, Se Jin; Yu, Chang Sik; Kim, Jin Cheon; Kim, Tae Won (Cancer research and treatment, 2017)
Although the mutation status of is highly concordant in primary and metastatic lesions, it has not been generalized to other major pathway genes. In this study, 41 genes were evaluated and the mutational profiles were compared in 46 colorectal cancer patients with paired surgical specimens of primary and metastatic lesions: synchronous (n=27) and metachronous (n=19) lesions. A high-throughput mass spectrometry-based genotyping platform validated by orthogonal chemistry, OncoMap v.4.4, was used to evaluate the formalin-fixed, paraffin-embedded surgical specimens. The patients' demographics, tumor characteristics, and microsatellite instability status were analyzed by a retrospective chart review. In this study,with OncoMap, mutationswere identified in 80.4% of patientswith the following frequency: (39.1%), (28.3%), (28.3%), (6.5%), (6.5%), and (4.3%). Although 19.6% (9/46) of the patients showed no gene mutations, 43.5% (20/46) and 37.0% (17/46) had mutations in one and two or more genes, respectively. The synchronous and metachronous lesions showed similar mutational profiles. Paired samples between primary and metastatic tumors differed in 7.4% (2/27) and 10.5% (2/19) for synchronous and metachronous according to OncoMap. These findings indicate the major pathway genes, including , , , , , and , are often concordant between the primary and metastatic lesions regardless of the temporal relationship of metastasis.